A systematic review of the roles of body image flexibility as correlate, moderator, mediator, and in intervention science (2011–2018) - Rogers, Courtney B.; Webb, Jennifer B.; Jafari, Nadia (Body image, 2018)
•A systematic literature review of body image flexibility is detailed.•The current literature minimally explores cross-cultural differences.•This literature base is largely concerned with study of maladaptive correlates.•Future research should emphasize diversity and development of valid measures. The emergence of body image flexibility into the positive body image nomenclature has innovatively expanded the conceptualization of how individuals may adaptively respond to body image threats. Given the notable growth of interest in researching this construct over nearly the past decade, the present analysis provides a systematic and critical review of evidence examining the roles of body image flexibility as correlate, mediator, moderator, and in intervention research. Results indicated that body image flexibility tended to demonstrate a pattern of relationships with correlates in directions predicted by its conceptualization and showed promise in functioning as both effect modifier and as an explanatory variable in the associations evaluated. Multiple studies demonstrated susceptibility to change following intervention. Although the current state of the literature is bound by notable limitations, the results of this review point to pertinent future steps in advancing the theory and application of body image flexibility scholarship.